Sequencing airborne DNA to monitor crop pathogens and pests - Amanda Mikko; Jose Antonio Villegas; Daniel Svensson; Edvin Karlsson; Per-Anders Esseen; Benedicte Riber Albrectsen; Ola Lundin; Mats Forsman; Anna Berlin; Per Stenberg (iScience)
Summary: Crop pests and diseases increasingly challenge the global food system. To prepare for and detect outbreaks, surveillance plays an important role. Traditional monitoring methods are often organism-specific, making large-scale monitoring of crop pathogens and pests impractical. We here investigate the potential for using shotgun sequencing of airborne eDNA for large-scale surveillance of crop pathogens and pests. We show that it is possible to detect DNA from all types of organisms in air, and that DNA can be classified down to species level. However, the accuracy of the identification is highly dependent on the quality of reference genomes of both the pathogens or pests, and their close relatives present in the region. Finally, we find that observed degree of crop damages correlate with amount of DNA from crop pathogens and pests in air, showing the promise of this approach for surveillance of all types of crop pathogens and pests.